Properties of risk capital allocation methods: Core Compatibility, Equal Treatment Property and Strong Monotonicity - Dóra Balog; Tamás László Bátyi; Péter Csóka; László Á. Kóczy; Péter Miklós Pintér (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2014)
In finance risk capital allocation raises important questions both from theoretical and practical points of view. How to share risk of a portfolio among its subportfolios? How to reserve capital in order to hedge existing risk and how to assign this to different business units? We use an axiomatic approach to examine risk capital allocation, that is we call for fundamental properties of the methods. Our starting point is Csóka and Pintér (2011) who show by generalizing Young (1985)'s axiomatization of the Shapley value that the requirements of Core Compatibility, Equal Treatment Property and Strong Monotonicity are irreconcilable given that risk is quantified by a coherent measure of risk. In this paper we look at these requirements using analytic and simulations tools. We examine allocation methods used in practice and also ones which are theoretically interesting. Our main result is that the problem raised by Csóka and Pintér (2011) is indeed relevant in practical applications, that is it is not only a theoretical problem. We also believe that through the characterizations of the examined methods our paper can serve as a useful guide for practitioners.
Keywords: C71; G10; 330; Coherent Measures of Risk; Risk Capital Allocation; Shapley value; Core; Simulation